Studi atas putusan Pengadilan Negeri Jakarta Selatan Nomor 10/PID.PRAP/2008/PN.JKT.SEL mengenai permohonan praperadilan PT. Inti Indosawit Subur terhadap Direktorat Jenderal Pajak Departemen Keuangan Republik Indonesia - ABIDIN, Muhammad Kilal ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Muhammad Kilal Abidin1, Marcus Priyo Gunarto2 and Isharyanto3 The research aims at identifying, analyzing, and gaining understanding on the legal position of the legality of search and confiscation in pre trial application. The research belongs to normative juridical research which emphasizes the analysis on secondary data which consists of primary material such as regulations and the court’s verdict, and secondary material such as library documents. The above secondary data are supported by primary data obtained from field study through semi structured interview. After the investigation carried out, the research concludes that, in both practice and theory of pre trial application, there is still a dualism concerning the legal position of the legality of search and confiscation. According to the articles proposed in Civil Law on pre trial application and some opinions from the law experts, the scope of pre trial application is limited and must be in accordance with the stipulation Article 77 No. 8 Year 1981. Therefore, it needs to be understood that there is no single article which arrange strictly whether the search and confiscation are approved materials to be proposed in pre trial application. As a result, based on Civil Law principles (lex scripta, lex stricta) and contra legem, the legality of search and confiscation is not in the scope of pre trial application. However, based on Article 95 Civil Law, toward an attempt to a searching and a confiscation can be proposed a pre trial application with a claim for replacements in a term of condition that the crime suit is on a clear and settled legal process, such as in the termination of legal process or when the judge has announced that the defendant proves not guilty. Keywords: tax, pre trial application, search, confiscation.